Network Governance in the HIV/AIDS Response in Batam City: A Social Network Analysis Approach - Samosir, Leonardo; Dian Prima Safitri; Okky Rizki Azizi (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2025)
This study analyzes the governance network involved in the HIV/AIDS response in Batam City using a Network Governance approach. HIV/AIDS remains a critical public health challenge in Indonesia, particularly in Batam, where its spread has shown significant increases. The research employs Social Network Analysis (SNA) to identify key actors, network structures, and the coordination patterns among stakeholders. Data were collected through structured interviews and field observations involving the Health Office, the AIDS Commission, and various non-governmental organizations. The findings indicate that the Health Office and the AIDS Commission function as central actors within the network, exhibiting high levels of centrality. However, collaboration is often hindered by bureaucratic constraints and limited program integration. The study recommends strengthening communication among actors, enhancing community participation, and establishing clear local regulations defining stakeholder roles. With a more inclusive and coordinated approach, the HIV/AIDS response in Batam City is expected to become more integrated and sustainable.